2013
DOI: 10.3109/10837450.2013.846375
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of particle size and encapsulation efficiency of vancomycin nanoparticles by response surface methodology

Abstract: The size and EE of vancomycin nanoparticles were optimized by the proposed procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 27 publications
3
34
0
4
Order By: Relevance
“…However, the findings indicated that if the drug was dissolved in CS solution and TPP was added afterward it had resulted in very low EE (<3%). Honary et al (2014) encapsulated vancomycin in CSNPs and reported 60–69% EE ( Honary et al, 2014 ) while 42–55% after encapsulation of 5-Fluorouracil. The well –characterized CSNPs were further investigated for their antipathogenic and anti-biofilm potential.…”
Section: Discussionmentioning
confidence: 99%
“…However, the findings indicated that if the drug was dissolved in CS solution and TPP was added afterward it had resulted in very low EE (<3%). Honary et al (2014) encapsulated vancomycin in CSNPs and reported 60–69% EE ( Honary et al, 2014 ) while 42–55% after encapsulation of 5-Fluorouracil. The well –characterized CSNPs were further investigated for their antipathogenic and anti-biofilm potential.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical optimization techniques are effectively used in diverse fields for various optimization processes, such as metabolite production, metabolite extraction, bacterial cell lysis, etc. [17][18][19] Keeping the potential of statistical optimization techniques in view, researchers have started using various designs of RSM for the formulation optimization of various nanodrug/delivery preparations [20][21][22][23][24][25][26]. However, artificial intelligence (AI)-based optimization techniques alone or in amalgamation with statistical optimization techniques have yet to be used in the formulation optimization of nanodrug preparations.…”
Section: Introductionmentioning
confidence: 99%
“…These data were contrary to some studies that indicate a direct relationship between the particle size and EE%; nevertheless, larger nanocarriers exhibit higher EE% . However, others indicated that not only particle size but also some other variables affect EE% . As the relationship between turbidity and lecithin concentration was linear, the trend of the relationship of turbidity and EE% was same as lecithin and EE%.…”
Section: Resultsmentioning
confidence: 99%